Students' Preferences Between Blackboard Teaching and PowerPoint Presentations: A Cross-Sectional Survey - Amos Masih; Nikhil Seth; Aditya Saxena; Prerna Baruah (International Healthcare Research Journal, 2020)
INTRODUCTION: With evolution of technology, teachers have, or are shifting to various methods other that blackboard teaching (e.g. PowerPoint, Over Head Projectors, Integrated Learning, Online Apps, etc)AIM: To assess students’ Preferences between blackboard teaching and PowerPoint Presentations among different university students in the city of Melbourne, AustraliaMATERIALS AND METHOD: Data was collected using a pre-tested and pre-validated questionnaire and distributed online to students studying in various Universities in Melbourne, Australia. Statistical tests involved the Shapiro-Wilk test, Independent samples t-test, multivariate linear regression and the Pearson’s correlation coefficient. The analysis was done using SPSS version 21.0.RESULTS: There were a total of 827 complete responses (response rate: 82.6%) and females formed a majority of the study population (62%). Majority of the students (53.1%) preferred PowerPoint presentations as compared to blackboard teaching (46.9%), although the difference was minimal; responses of females was statistically significant (p=0.02). Significant differences (p=0.03) were also observed as 58.8 % students considered blackboard teaching more interesting as compared to PowerPoint Lectures.CONCLUSION: Students preferred PowerPoint presentations as compared to Blackboard teaching and the teachers should aim to make it as interesting as possible and allow student interaction in between.